Honour-based violence and forced marriages : community and restorative practices in Europe - Rigoni, Clara (London ; New York : Routledge, 2023)
"In the last 20 years, the related phenomena of honour-based violence and forced marriages have received increasing attention at the international and European level. Punitive responses towards this type of violence have been adopted, including ad hoc criminalisation and legislation containing direct references to the concepts of honour, culture, and tradition. However, criminal law-based responses present several shortcomings and have often disregarded the specific needs that victims of such crimes might encounter. This book examines the possibility of using alternative programmes to address cases of honour-based violence and forced marriages. After reviewing previous existing literature, it presents new empirical data. Introducing a case study from the United Kingdom, the book recalls the debate on Sharia Councils and the Muslim Arbitration Tribunal, but examines instead other community-based secular programmes. By comparison, a study from Norway on the work of the National Mediation Agency and the so-called Cross-Cultural Transformative Mediation model is investigated as part of a larger multi-agency approach. Ultimately, in an attempt to reconcile pluralism and the rule of law, the book proposes effective ways to tackle honour crimes based on cooperation and individualisation of the proceedings, and capable of improving women's access to justice and reducing secondary victimisation"--Publisher's description.
Honour-Based Violence and Forced Marriages -- The Accommodation of Normative Plurality within European Legal Systems -- The Accommodation of Normative Plurality through Extra-Legal Instruments : Alternative Dispute Resolution Mechanisms and Restorative Justice -- The United Kingdom -- Norway -- Comparative Overview of the Findings -- Discussion of the Findings and Conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Domestic relations -- Europe; Family violence -- Law and legislation -- Europe; Forced marriage -- Law and legislation -- Europe; Muslims -- Legal status, laws, etc. -- Europe; Multiculturalism -- Law and legislation -- Europe; Dispute resolution (Law) -- Europe; Restorative justice -- Europe; Domestic relations -- Great Britain; Domestic relations -- Norway